Entrepreneurship in China: A Review of the Role of Normative Documents in China’s Legal Framework for Encouraging Entrepreneurship - Ernest Kenneth-Southworth; Casey Watters; Chuning Gu (Entrepreneurial Business and Economics Review, 2018)
Objective: The objective of the article is to provide an overview of the Chinese legal framework while examining the laws and legal provisions influencing entrepreneurship in China for both Chinese and foreigners, arguing that the current legal environment encourages domestic entrepreneurship and foreign investment.